Voluntary vasectomy rethinking "Pagkalalaki" among married cebuano - Aguilar, Elmira Judy T. (2006)
This qualitative study intends to determine the ways in which concepts of masculinity have shaped the contraceptive choice of men for vasectomy. The findings show that masculinity is defined as being responsible husband and father who can provide for the basic needs of his family such as food, clothing, and education. Thus, men's direct participation in family planning is basically due to economic reasons because of his responsibility to take care of his familys' future.

Wives and health providers have significantly contributed in men's decision to undergo vasectomy. Wives provided information about the procedure and supported their husbands' decision to have a vasectomy. Health providers thoroughly explained the procedure and corrected myths and misconceptions regarding the procedure which gave men an assurance that vasectomy is safe and reliable. In-laws and friends did not have noteworthy influence on men's decision.

It did not take long for men to decide on undergoing vasectomy after they received information about it. This was especially true when misconceptions associated with having vasectomy such as failure to have an erection, loss of physical strength and equating it with castration, to name a few, were corrected. After having vasectomy, men still saw themselves as masculine and rightfully being rsponsible husbands and fathers.